Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I was reading the solution of a problem and I can't figure out how to go from here:

$k^4 + 2k^3 -k^2 - 2k + 1$


$((k^2 + k) -1)^2$

I guess it's using the complete-the-square method but I've only used that with quadratic expressions.

share|cite|improve this question
$k^4 + 2k^3 -k^2 - 2k + 1=k^4 + 2k^3 +k^2 -2k^2 - 2k + 1=k^4 + 2k^3 + k^2 -2(k^2 + k) + 1$... – J. M. Oct 16 '11 at 16:52

The symmetry of the sequence of coefficients $(1,2,-1,-2,1)$ with respect to its middle term suggests to use the change of variables $x=k-\frac1k$. The fourth degree polynomial $P(k)$ you are interested in is $P(k)=k^2Q(k)$ with $Q(k)=k^2+2k-1-\frac2k+\frac1{k^2}$. One recognizes $2k-\frac2k=2x$. To deal with $k^2+\frac1{k^2}$, note that $x^2=k^2-2+\frac1{k^2}$ hence $Q(k)=x^2+2x+1=(x+1)^2$.

Hence, $P(k)=k^2(x+1)^2=(kx+k)^2=(k^2-1+k)^2$.

Likewise, every polynomial $$ P(k)=a_0+a_1k+a_2k^2+\cdots+(-1)^{n-2}a_{2}k^{n-2}+(-1)^{n-1}a_{1}k^{2n-1}+(-1)^na_{0}k^{2n} $$ of degree $2n$ is $P(k)=k^nQ(x)$ where $Q(x)$ is a polynomial of degree $n$ and $x=k-\frac1k$ and every polynomial $$ P(k)=a_0+a_1k+a_2k^2+\cdots+a_{2}k^{n-2}+a_{1}k^{2n-1}+a_{0}k^{2n} $$ of degree $2n$ is $P(k)=k^nR(y)$ where $R(y)$ is a polynomial of degree $n$ and $y=k+\frac1k$. The polynomials are easily computed using the expressions of $x^i$ and $y^i$ as sums of powers of $k$ and $\frac1k$, for successive integer values of $i\geqslant0$.

share|cite|improve this answer
Thanks a lot. This belongs to an intro to discrete maths book. The other problems were much easier but I got lost at this step. – mathnoob Oct 16 '11 at 17:21

$k^4+2k^3−k^2−2k + 1 = k^4 + (k^2 - 2k^2) + 2k^3 - 2k + 1 \quad \Rightarrow$

$k^4+2k^3−k^2−2k + 1 = (k^4 - 2k^2 + 1) + 2k(k^2 - 1) + k^2$

$= (k^2 - 1)^2 + 2(k^2 - 1)k + k^2 = (k^2 - 1 + k)^2 = ((k^2 + k) - 1)^2$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.